PENGARUH PERAN SOFT SKILL TERHADAP KINERJA KARYAWAN PADA PT. MEPPO-GEN - Ghofur, Abdul; Nugroho, Moh Taufan; Rista, Nadia (Jurnal Daya Saing, 2025)
Employee performance is often shaped by more than just technical ability. In today’s fast-paced work environment, non-technical competencies or soft skills significantly influence productivity, collaboration, and individual accountability. This study explores the relationship between soft skills and employee performance at PT. Meppo-Gen using a quantitative survey involving all 62 employees. The research instruments were proven valid and reliable. The data were normally distributed and met the assumptions of linearity. Simple linear regression analysis produced an R² value of 0.788, indicating that soft skills account for 78.8% of the variation in employee performance. A positive regression coefficient confirms that stronger soft skills are linked to higher performance outcomes. Key contributors include communication, leadership, teamwork, time management, and problem-solving, all of which support performance in terms of quality, quantity, timeliness, and responsibility. These findings emphasize that soft skills form the foundation of a productive and resilient workforce capable of adapting to changing organizational demands.